Comparison of Two Tonometers in the Evaluation of 24-Hour Intraocular Pressure and Mean Ocular Perfusion Pressure in Patients with Thyroid-Associated Ophthalmopathy - Weijie Liu; Yao Zhou; Xiaozhou Hu; Haochen Jin; Jie Ye; Mingna Xu; Zihui Liu; Wencan Wu; Yunhai Tu (Journal of Ophthalmology)
Purpose. The aim of the study is to compare a non-contact tonometer (NCT) and goldmann applannation tonometer (GAT) in the evaluation of intraocular pressure (IOP) and mean ocular perfusion pressure (MOPP) in patients with thyroid-associated ophthalmopathy (TAO). Methods. In this study, a total of 30 patients (16 females and 14 males) were recruited. All patients underwent a routine ophthalmic assessment and their medical history was acquired. Clinical assessment included the 24-hour measurement of intraocular pressure and blood pressure, an orbital computed tomography (CT) scan, and a visual field (VF）test. Patients were divided into two groups according to their visual field test results: a defect group with mean deviation (MD) of visual field −2 dB or lower and a normal group with MD over −2 dB. Results. Bland–Altman’s analysis showed similar results of IOP at every time point and revealed an agreement of mean IOP between the two tonometers (the deviation in the mean IOP between the two tonometers was 1 mmHg, with 95% limits of agreement of 8.8 to −6.8 mmHg). The 24-hour MOPP SD value in NCT (2.28) and GAT (1.77) showed that the two instruments had the same diagnostic efficacy (100% sensitivity, 95.8% specificity). The areas under the receiver operator characteristic (ROC) curve of the 24-hour mean ocular perfusion pressure (MOPP) SD (GAT: 0.778, NCT: 0.713; z = 0.669, P=0.504), 24-hour MOPP fluctuation (GAT:0.683, NCT:0.757; z = 0.963, P=0.336) measured by GAT and NCT had no significant difference between the two tonometers. Conclusions. The measurement of IOPs, MOPPs, and their diagnostic efficacy of visual field defect showed consistency between NCT and GAT. The study highlights the importance of monitoring the 24-hour MOPP and IOP in TAO patients. Furthermore, it suggests that the less invasive NCT can replace GAT as a long-term monitoring device in TAO patients.